Vietnam’s first ‘AGRITECHNICA ASIA Live’: An International Success - International Rice Research Institute (CGIAR System Organization, 2022)
CAN THO, Vietnam, September 1, 2022) – Almost 4,000 attendees; 80 companies with machinery demonstrations and displays from tillage and sowing to harvesting and grain handling; 22-hectare trial and demonstration plots – conferences on mechanization – official opening by Minister of Agriculture – 24-26 August in Mekong Delta, Vietnam.